Cannabinoids As Potential Treatment for Chemotherapy-Induced Nausea and Vomiting - Rock, Erin M.; Parker, Linda A. (Frontiers in Pharmacology, 2016)
Despite the advent of classic anti-emetics, chemotherapy-induced nausea is still problematic, with vomiting being somewhat better managed in the clinic. If post-treatment nausea and vomiting are not properly controlled, anticipatory nausea—a conditioned response to the contextual cues associated with illness-inducing chemotherapy— can develop. Once it develops, anticipatory nausea is refractive to current anti-emetics, highlighting the need for alternative treatment options. One of the first documented medicinal uses of Δ9-tetrahydrocannabinol (Δ9-THC) was for the treatment of chemotherapy-induced nausea and vomiting, and recent evidence is accumulating to suggest a role for the endocannabinoid system in modulating chemotherapy-induced nausea and vomiting. Here, we review studies assessing the therapeutic potential of cannabinoids and manipulations of the endocannabinoid system in human patients and pre-clinical animal models of nausea and vomiting.